Influence of foliar application of gibberellic acid, calcium and boron on fruit drop, yield and quality attributes of aonla (Emblica officinalis) cv. NA 7 - TRIPATHI, V K; PANDEY, S S; KUMAR, AJAY; DUBEY, VISHAL; TIWARI, PRAKASH (The Indian Journal of Agricultural Sciences, 2018)
A study was undertaken to examine the influence of foliar application of gibberellic acid (GA3), calcium and boron on fruit drop, yield and quality attributes of aonla (Emblica Officinalis Gaertn.) cv. NA 7 during two successive years, i.e. 2014-15 and 2015-16 on 15 year old plant of aonla cv. NA 7 at CSAUA&T, Kanpur (Uttar Pradesh), India. The experiment was laid out in randomized block design with three replications and 10 treatments, viz. GA3 (25, 50 and 100 ppm), calcium chloride (0.5, 1.0 and 1.5 %) and borax (0.2, 0.4 and 0.6 %) including a control. Significantly reduced fruit drop (66.2 %) with increased fruit retention (29.85%) and specific gravity (1.06 g/cm3) was observed in plants treated with borax at 0.6%. Maximum fruit length (3.78 cm), width (3.89 cm), weight (30.90 g), volume (29.46 cc), pulp weight (29.16 g), total sugars (12.92 %), TSS (14.90 0Brix), fruit yield (80.50 kg/plant) with more moisture contents (94.04 %) was recorded in fruits produced from GA3 50 ppm treated plants, whereas, GA3 @ 100 ppm treatment reduces the titratable acidity (1.56 %) and stone weight (1.45 g) but increases the pulp: stone ratio (18.44%). Fruits with maximum ascorbic acid (608 mg/100g pulp) contents were produced from the plants treated with calcium chloride 1.5 % in the month of August in northern plains of India.